The Implementation Of Ummi Method In Learning Reading Quran In SDI Kartika Nawa Turen Malang - Nahdiyah, Fachrin; Acetylena, Sita; Husni, M. (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to describe the implementation of the Ummi Method in SDI Kartika Nawa Turen Malang. The student’s achievement, the advantages and the weakness of Ummi method. This study is qualitative research by using some instruments: observation, interview, and documentation. The results of this study are the implementation of Ummi method based on ten pillar: goodwill management, teacher certification, stage good and true, clear and measurable targets, mastery consistent learning, adequate time, ratio proportional teachers and students, internal control and externally, progress reports for each student and reliable coordinator. Students’ studies Quran based on their grades after having a placement test. The advantage of the Ummi method is that the teachers get easily in teaching Qur an because there is a guideness learning and teaching process. Besides, there is controlling from three external and internal. The weakness of Ummi method in SDI Kartika Nawa is the lackness of Ummi teachers and the amount of cost in the implementation of Ummi method.